Organised crime, criminal procedure, and prisons: prosecuting and punishing organised criminal groups - Schloenhardt, Andreas; Weißer, Bettina; Stempkowski, Monika; Ege, Gian (Transnational criminal justice, 2025)
"This book explores a range of topics relating to the prosecution and trial of organised crime and the punishment, especially imprisonment, of members of organised criminal groups. Organised crime poses particular challenges to the criminal justice system. While much of the attention of policy-makers, legislators, law enforcement, and the media is on criminalisation and investigation, much less attention, including academic analysis, has been devoted to the unique problems posed by organised crime to criminal procedure and to the prison system. This book gives particular attention to the role and powers of prosecutors and the judiciary, measures relating to criminal proceedings, international cooperation, sentencing, and the situations in prisons. The book will be a valuable guide for academics, researchers and policy-makers working in the areas of organised crime, international criminal justice, criminal procedures, and prisons"--